Answer: The correct option is
(c)
![\triangle CDE\sim \triangle FGH.](https://img.qammunity.org/2020/formulas/mathematics/middle-school/vrjx6kxzer3dc3a1xxk6bjfe00x5yhcpgq.png)
Step-by-step explanation: We are given to write a similarity statement for the triangles shown in the figure.
In the given triangles, we have
m∠C = 60°, m∠D = 53°, m∠F = 60° and m∠H = 67°.
Fist, we have to fin d the measures of angles E and G.
From angle sum property of a triangles, we can write
![m\angle C+m\angle D+m\angle E=180^\circ\\\\\Rightarrow 60^\circ+53^\circ+m\angle E=180^\circ\\\\\Rightarrow 113^\circ+m\angle E=180^\circ\\\\\Rightarrow m\angle E=180^\circ-113^\circ\\\\\Rightarrow m\angle E=67^\circ.](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jkse6hsn7p6ct7uw5cnnivos71m0fh27x3.png)
Similarly, we have
![m\angle F+m\angle G+m\angle H=180^\circ\\\\\Rightarrow 60^\circ+m\angle G+67^\circ=180^\circ\\\\\Rightarrow 127^\circ+m\angle G=180^\circ\\\\\Rightarrow m\angle G=180^\circ-127^\circ\\\\\Rightarrow m\angle G=53^\circ.](https://img.qammunity.org/2020/formulas/mathematics/middle-school/l8f0nrurv0rpixts39wjeo8wxbkb8xh0zt.png)
So, we get
m∠C = m∠F,
m∠D = m∠G
and
m∠E = m∠H.
Therefore, by angle-angle-angle similarity postulate. we get
![\triangle CDE\sim \triangle FGH.](https://img.qammunity.org/2020/formulas/mathematics/middle-school/vrjx6kxzer3dc3a1xxk6bjfe00x5yhcpgq.png)
Thus, option (c) is CORRECT.